Life stage-specific glycosylation of extracellular vesicles from Schistosoma mansoni schistosomula and adult worms drives differential interaction with C-type lectin receptors DC-SIGN and MGL - Kuipers, Marije E.; Nguyen, D. Linh; van Diepen, Angela; Mes, Lynn; Bos, Erik; Koning, Roman I.; Nolte-’t Hoen, Esther N. M.; Smits, Hermelijn H.; Hokke, Cornelis H. (Frontiers in Molecular Biosciences, 2023)
Schistosomes can survive in mammalian hosts for many years, and this is facilitated by released parasite products that modulate the host’s immune system. Many of these products are glycosylated and interact with host cells via C-type lectin receptors (CLRs). We previously reported on specific fucose-containing glycans present on extracellular vesicles (EVs) released by schistosomula, the early juvenile life stage of the schistosome, and the interaction of these EVs with the C-type lectin receptor Dendritic Cell-Specific Intercellular adhesion molecule-3-Grabbing Non-integrin (DC-SIGN or CD209). EVs are membrane vesicles with a size range between 30-1,000 nm that play a role in intercellular and interspecies communication. Here, we studied the glycosylation of EVs released by the adult schistosome worms. Mass spectrometric analysis showed that GalNAcβ1–4GlcNAc (LacDiNAc or LDN) containing N-glycans were the dominant glycan type present on adult worm EVs. Using glycan-specific antibodies, we confirmed that EVs from adult worms were predominantly associated with LDN, while schistosomula EVs displayed a highly fucosylated glycan profile. In contrast to schistosomula EV that bind to DC-SIGN, adult worm EVs are recognized by macrophage galactose-type lectin (MGL or CD301), and not by DC-SIGN, on CLR expressing cell lines. The different glycosylation profiles of adult worm- and schistosomula-derived EVs match with the characteristic glycan profiles of the corresponding life stages and support their distinct roles in schistosome life-stage specific interactions with the host.